Pengaruh Digital Marketing terhadap Keputusan Pembeli pada UMKM Q Raden Kaos Polos di Kota Serang - Riki Gana Suyatna; Berliana Pebriyanti; Dede Rifki; Ismalia Nur Hidayah; Sri Mulyaningsih (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
The purpose of this study was to determine the effect of digital marketing on purchasing decisions at Q Raden kaos polos. The method used in this study is quantitative research methods and instruments used, namely questionnaires measured using a Likert scale. The analysis used in this study is simple linear regression analysis. The number of respondents in this study were 100 respondents consisting of men and women of various ages and occupations. From the results of data analysis obtained the coefficient of determination (R Square) of 0.194, so that it can be interpreted that E-commerce has a very low influence on purchasing decisions at Q Raden kaos polos. The results of the simple linear regression analysis, a positive regression coefficients is obtained so it can be said that the direction of the influence E-Commerce variables on the purchasing decision variable positive.